Partial retirement and pension policy in industrialized countries - Latulippe, Denis (2000)
Examines the advantages, disadvantages and costs of partial retirement. Discusses policies that affect partial retirement, particularly through its interaction with social security and training. Reviews the salient features of partial retirement policies in selected industrialized countries.